Dr. Phung Manh Cuong — Deep Plane Facelift — Ho Chi Minh City - Cuong, Phung Manh (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Phung Manh Cuong, practicing in Ho Chi Minh City, Vietnam. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003262; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; vietnam; ho chi minh city